Influence of Biologically Oriented Preparation Technique on Peri-Implant Tissues; Prospective Randomized Clinical Trial with Three-Year Follow-Up. Part II: Soft Tissues - Agustín-Panadero, Rubén (J Clin Med, 2019)
Purpose: The objective of this prospective randomized clinical trial (RCT) was to analyze and compare the clinical behavior of three types of prosthesis supported by single implants in the posterior region after three years of functional loading. Materials and methods: Seventy-five implants were divided into three groups according to the type of prosthetic restoration: screw-retained crown (group GS); cemented crown without finishing line (biologically oriented preparation technique) (group GBOPT); and conventional cemented crown with finishing line (group GCC). After three years in function, clinical parameters (presence of keratinized mucosa, probing depths, bleeding on probing, and radiographic bone loss) were compared between the three experimental groups. The possible correlation between soft tissue clinical parameters and bone loss was also analyzed. Results: Statistical analysis found significant differences in clinical parameters between the different types of crown, with the cemented restoration without finishing line (BOPT) presenting fewer complications and better peri-implant health outcomes including: significantly different KMW data (mm), with significant differences between groups GBOPT and GCC (p < 0.001, Kruskal–Wallis test), with GBOPT obtaining larger quantities of keratinized mucosa (KM); statistically significant differences in probing depth (PD) values between groups GBOPT and GCC (p = 0.010, Kruskal–Wallis test); significant differences in bleeding on probing (BOP) between groups GBOPT and GCC (p = 0.018, Chi(2) test) in favor of GBOPT. Conclusions: Soft tissue behavior around implants is related to the type of prosthetic restoration used, with cemented prostheses with BOPT presenting better peri-implant soft tissue behavior.